Effects of paclobutrazol on ethylene sensitivity of potted pepper cultivars (Research, Society and Development, 2022)
Exposure to ethylene of ornamental plants is one of the factors that affect the life cycle post-production of these plants. The aim of this work was to evaluate the effects of paclobutrazol (PBZ) on the ethylene related responses of ten pepper cultivars of the genus Capsicum and one Solanum by simulating transport and commercialization. The cultivars were treated with PBZ at concentrations of 0, 5, 10 and 20 mg L-1 applied on the potted cultivation substrate. When the plants had 30% of ripe fruits, they were transferred to a 90 L sealed container and treated with 10 μL L-1 ethylene for 48 hours and then kept at room temperature.  Percentages of leaf (LA) and fruit abscission (FA) the plants were recorded at every two days (48h, 96h and 144h). The design used was completely randomized, in an 11 x 4 factorial scheme. The PBZ did not completely inhibit the deleterious effects of exogenous ethylene on plants. However, the ‘Pérola Negra’ showed moderate sensitivity for leaf and fruit abscission, and the ‘Bode Vermelha’ for leaf abscission at a concentration of 10 mg L-1. PBZ prevented partially the abscission of fruits of the ‘Pirâmide Ornamental’ pepper at rates of 5 and 10 mg L-1, and ‘Tabasco’ pepper at a concentration of 10 mg L-1. In addition, cultivars showed darker foliage when treated with PBZ.